Voice-Based Email System for Blind People: A Human-Centered Assistive Communication Platform - Verma, Asmit; Yadav, Ashwani Kumar; Shukla, Harish; Rana, Sadhana (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study introduces a novel voice-operated email system specifically designed to support people with visual impairments in accessing digital communication independently. Utilizing advanced speech recognition and text-to-speech technologies, the system allows users to seamlessly compose, send, receive, and manage emails using verbal commands alone. Developed in Python and powered by key libraries such as speech_recognition, gTTS, and imaplib, the system provides an intuitive, hands-free experience. Testing demonstrated high recognition accuracy and ease of operation even in moderate noise conditions, highlighting its potential to enhance inclusivity and digital autonomy for the visually impaired community.